2013
DOI: 10.1136/bmj.f2424
|View full text |Cite
|
Sign up to set email alerts
|

Day of week of procedure and 30 day mortality for elective surgery: retrospective analysis of hospital episode statistics

Abstract: Objectives To assess the association between mortality and the day of elective surgical procedure.Design Retrospective analysis of national hospital administrative data.Setting All acute and specialist English hospitals carrying out elective surgery over three financial years, from 2008-09 to 2010-11.Participants Patients undergoing elective surgery in English public hospitals.Main outcome measure Death in or out of hospital within 30 days of the procedure.Results There were 27 582 deaths within 30 days after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
244
5
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(264 citation statements)
references
References 19 publications
(35 reference statements)
11
244
5
4
Order By: Relevance
“…In the United Kingdom, each day following Monday was associated with an independent increase in the odds of 30-day mortality, with a marked relative increase (compared with Monday) of 44% on Friday and 82% on weekend days. 18 In the United States, patients whose operations occurred on Friday were more likely to die after surgery than those whose operations occurred on Monday, Tuesday, or Wednesday. 19 Although any causal factors underlying this relationship have not been fully elucidated, they are hypothesized to be related to gaps in the healthcare system which are potentially due to low staffing levels and physician cross-coverage of patients occurring during the weekend after surgery.…”
Section: Résumémentioning
confidence: 99%
See 2 more Smart Citations
“…In the United Kingdom, each day following Monday was associated with an independent increase in the odds of 30-day mortality, with a marked relative increase (compared with Monday) of 44% on Friday and 82% on weekend days. 18 In the United States, patients whose operations occurred on Friday were more likely to die after surgery than those whose operations occurred on Monday, Tuesday, or Wednesday. 19 Although any causal factors underlying this relationship have not been fully elucidated, they are hypothesized to be related to gaps in the healthcare system which are potentially due to low staffing levels and physician cross-coverage of patients occurring during the weekend after surgery.…”
Section: Résumémentioning
confidence: 99%
“…19 Although any causal factors underlying this relationship have not been fully elucidated, they are hypothesized to be related to gaps in the healthcare system which are potentially due to low staffing levels and physician cross-coverage of patients occurring during the weekend after surgery. 10,18,[23][24][25] Unplanned admissions or returns to the hospital or ED for surgical complications are considered to be important quality indicators in ambulatory surgery programs 1,26,27 ; however, investigations are lacking on the impact of the day of the week on outcomes after ambulatory surgery. In this study, we hypothesized that the day of the week on which ambulatory surgery was performed would impact postoperative outcomes, primarily because patients having surgery late in the week may have limited access to care in a surgeon or family physician's office over the subsequent weekend.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation
“…3,[32][33][34][35] However, much of the evidence on the effect of weekend admission has been limited in key respects. First, it tends to be cross-sectional and there is therefore limited information on the trends in disparities over time.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Indeed, more recent work addressing the effect of the day of the week as a factor in surgical outcomes has suggested that the odds of death are higher following elective surgery on a Friday compared with other days of the week. 3 This ''Friday effect'' and the accompanying concerns over reduced staffing levels on weekends have been suggested as the main explanation for the differences in outcomes and have led to calls for increased weekend staffing. For example, in the United Kingdom (UK), the clinical director of the National Health Service has called this need for more staffing his numberone priority.…”
mentioning
confidence: 99%